Cognitive Consequences in Children with Epilepsy (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Some epilepsy is, in general, often associated with cognitive problems that can also affect a patient’s adjustments. Epileptic seizures result from an excessive, synchronous discharge of cerebral neurons. Interictal paroxysmal electroencephalogram (EEG) abnormalities are regarded as a correlate of persistent pathological neuronal discharges. Thus, correlation between cognitive deterioration and seizure severities/EEG paroxysmal abnormalities should be investigated. We have previously measured frontal/prefrontal lobe volumes using three-dimensional (3D)-magnetic resonance imaging (MRI) in children with benign childhood epilepsy with centrotemporal spikes, epilepsy with continuous spike-waves during slow sleep, frontal lobe epilepsy, and Panayiotopoulos syndrome, and confirmed that longer active seizure period as frequent spike-waves coupled with the occurrence of frequent seizures and presence of status epilepticus may be associated with prefrontal lobe growth disturbance, which relates to cognitive impairments. These findings suggest that seizure severities such as repeated seizures and presence of status epilepticus, and the subclinical paroxysmal EEG abnormalities may induce prefrontal lobe growth disturbance, which leads to intellectual impairments. Achieving better seizure control and remission for paroxysmal EEG abnormalities is a key to improve quality of life (QOL) in children with epilepsy. From the perspective of decreased cognitive problems and improving QOL, management may be required to remit seizures and paroxysmal EEG abnormalities as soon as possible to achieve optimal prognosis in epilepsy.